LITERATUR REVIEW : ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI AUDIT JUDGMENT DI BADAN PEMERIKSAAN KEUANGAN (BPK) - Pambarumni, Anisa Syaiffa; Suryatimur, Kartika Pradana (Transpublika Publisher, 2023)
In the realm of public financial oversight, the Supreme Audit Agency (BPK) plays a pivotal role, tasked with ensuring the integrity and transparency of financial practices. Within the complex landscape of auditing, the exercise of judgment becomes paramount, especially in situations marked by uncertainty and limited data access. This research aims to find out empirically about the factors that influence audit judgment at the Supreme Audit Agency (BPK), especially gender factors, obedience pressure and auditor experience. Audit judgment is needed when dealing with uncertainty or limited data information obtained, and the audit is also required to make assumptions that are used to make judgments and evaluate judgments. The research was carried out using the literature review method where the research was carried out by collecting a number of articles related to the problems raised by the researcher. The results of the previous literature review show that there are several things that influence audit judgment at BPK such as gender, pressure and auditor experience.